The role of muscle forces in neck comfort for static seating: a pilot study - Alawneh, Obidah; Rassas, Basaam; Zhong, Xianzhi; Xi, Jason; Faieghi, Reza; Xi, Fengfeng (Frontiers in Mechanical Engineering, 2024)
Aircraft seats play a key role in the competition between aircraft companies seeking to differentiate themselves in terms of passengers' inflight experience. The seat design process relies on computational and experimental methods based on subjective measures, such as comfort rating questionnaires, and objective comfort indicators of seat-occupant interaction, such as contact pressure distribution and muscle activation. Previous studies around muscle activity for seating comfort assessment have primarily focused on more active scenarios or active systems. As such, there are limited studies about the role of muscle force in normal and relaxed sitting conditions, common in aircraft settings. This paper explores the relationship between activities of the neck muscles, sternocleidomastoid, and upper trapezius, measured from human participants seated sedentarily on conventional business aircraft seats and their perceived comfort with different backrest inclinations. The results show, for normal seating without neck pillow, no significant association is found between the backrest inclination and the neck's comfort or muscle activation. For general seating across different backrest inclinations, a negative medium correlation between muscle activation and comfort is found in upper trapezius (R=-0.5332, P=0.0187). This work serves as a pilot study of this new approach of comfort evaluation using muscle feedback in seat designing processes and highlights the posterior's effect to seating experience in the neck region.